Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Layanan Akademik - Dian Evy Nofitasari; Muhamad Fauzen (PT Rizkarya Cendekia Pustaka, 2025)
This study aims to describe and analyze the leadership strategies of the principal in improving the quality of academic services at Madrasah Aliyah Kholafiyah Hasaniyah, Probolinggo Regency, Indonesia. The research was motivated by the urgency of effective school leadership, especially in rural Islamic educational institutions, to enhance academic excellence through transformative and contextual approaches. This study employed a qualitative descriptive method using a case study design. Data were collected through in-depth interviews with the school principal, vice principal for curriculum, five teaching staff, one school committee representative, and two students, as well as observations and documentation analysis. The findings reveal that the principal applied transformational leadership strategies, emphasizing moral example, collaborative decision-making, mentoring-based teacher development, and the integration of educational technology. A participatory leadership style fostered a positive school climate, strengthened collective commitment, and encouraged pedagogical innovation among teachers. Moreover, the school committee played an active role in strategic academic planning and community engagement. In conclusion, leadership strategies grounded in Islamic values, clear institutional vision, and collaborative governance significantly contribute to sustainable improvements in academic service quality. This research provides practical and theoretical implications for developing leadership models in Islamic educational institutions, particularly in rural settings.